1974
DOI: 10.1037/h0036982
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus preexposure and discrimination learning by domestic chicks: Effect of varying interstimulus time.

Abstract: Groups of domestic chicks were preexposed to moving objects on Days 1-5 after hatching. Only one object was visible at a time, and the time between the appearance of one stimulus and the immediately succeeding appearance of the other was called the "interonset time". Chicks which had been preexposed to both discriminanda in rapid alternation (interonset time of V4 min.) learned a subsequent discrimination task more slowly than chicks familiar with neither stimulus; chicks preexposed to both discriminanda at se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0
2

Year Published

1976
1976
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 21 publications
3
26
0
2
Order By: Relevance
“…It has been shown that chicks will blend two objects if they appear in close temporal proximity to each other (Chantrey 1974;Stewart et al 1977). This temporal dependency alone is consistent with the idea that the object recognition system uses hysteresis to develop invariant representations of objects.…”
Section: Introductionsupporting
confidence: 68%
“…It has been shown that chicks will blend two objects if they appear in close temporal proximity to each other (Chantrey 1974;Stewart et al 1977). This temporal dependency alone is consistent with the idea that the object recognition system uses hysteresis to develop invariant representations of objects.…”
Section: Introductionsupporting
confidence: 68%
“…According to ten Cate and co-workers (ten Cate 1986(ten Cate , 1987Hollis et al 1991) 'ditherers' develop a mixed or a double mental representation of objects which can be used for the selection of an appropriate sexual partner. When, as in our studies, the two exposures are separated by a substantial amount of time, it is more likely that a double instead of a mixed representation is developed (Chantrey 1974;Hollis et al 1991). According to the analysis-recognition-execution model (Bateson 1987(Bateson , 1990(Bateson , 1991 such representations are linked, in a second step, to an executive system which controls sexual behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…213-216). However, the fact that imprinting training with both of the to-be-discriminated cues can result in a retardation of subsequent discrimination learning (Chantrey, 1974; a finding that we have recently confirmed with the type of stimuli used in Experiment 2), is sufficient to make one question the general utility of habituated fear as an explanation of the effects of imprinting training on discrimination learning.…”
Section: 37mentioning
confidence: 80%